Effects of a 12-week dance program with two weekly frequency protocols on fine motor competence and balance in preschool children: A randomized controlled trial - Anđela Đošić; Danijela Živković; Slavoljub Uzunović; Mladen Živković; Nenad Đorđević; Saša Pantelić (PLoS ONE, 2025)
This study examined the effects of structured dance programs on motor competence in preschool children. In a 12-week randomized controlled trial, 80 children were randomly assigned to two dance intervention groups (EG1: 2 × 35 min/week; EG2: 3 × 25 min/week) or a control group (CG) following the standard physical education curriculum. Fine motor skills, fine motor integration, and balance were assessed using the Bruininks–Oseretsky Test of Motor Proficiency, administered both before and after the intervention. Significant improvements were observed in EG1 for fine motor precision (p < 0.001), fine motor integration (p = 0.022), and static balance (standing on one leg on a balance beam with eyes open; p < 0.001). EG2 showed significant gains in dynamic balance (walking forward on a line; p < 0.001). Both dance programs enhanced preschoolers’ motor competence compared to the control, with higher session volume producing superior outcomes. These results support integrating structured dance sessions into preschool curricula to effectively enhance motor competence, offering a practical strategy to promote physical development in early childhood.